2001
DOI: 10.1038/88486
|View full text |Cite
|
Sign up to set email alerts
|

Human brain activity time-locked to perceptual event boundaries

Abstract: Temporal structure has a major role in human understanding of everyday events. Observers are able to segment ongoing activity into temporal parts and sub-parts that are reliable, meaningful and correlated with ecologically relevant features of the action. Here we present evidence that a network of brain regions is tuned to perceptually salient event boundaries, both during intentional event segmentation and during naive passive viewing of events. Activity within this network may provide a basis for parsing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
453
3
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 474 publications
(495 citation statements)
references
References 23 publications
37
453
3
2
Order By: Relevance
“…The chronology‐judgment task required retrieving the event sequences of many complex stimuli (scenes) that entail high‐level conceptual/hierarchical relationships between them [Swallow et al, 2011; Zacks et al, 2001]. The precuneus was previously found to activate in our LTM protocol that used the same temporal order judgment [Kwok, et al, 2012; and see also results of the conjunction analyses].…”
Section: Discussionmentioning
confidence: 95%
“…The chronology‐judgment task required retrieving the event sequences of many complex stimuli (scenes) that entail high‐level conceptual/hierarchical relationships between them [Swallow et al, 2011; Zacks et al, 2001]. The precuneus was previously found to activate in our LTM protocol that used the same temporal order judgment [Kwok, et al, 2012; and see also results of the conjunction analyses].…”
Section: Discussionmentioning
confidence: 95%
“…Such nonlinear transient components of the BOLD response are well-known for cognitive tasks (Courtney et al, 1997;Postle, Zarahn and D'Esposito, 2000;Konishi, Donaldson and Buckner, 2001;Posse et al, 2001;Huettel, Guzeldere, McCarthy, 2001;Shulman et al, 2001;Zacks et al, 2001;Calhoun et al, 2001Calhoun et al, , 2002ad'Avossa, Shulman and Corbetta, 2003;Krasnow et al, 2003;Calhoun et al, 2004a;Cabeza et al, 2004;Chen and Desmond, 2005;Fox et al, 2005;Meegan and Honsberger, 2005;Scheibe et al, 2006;Vuilleumier et al, 2005) but we are not aware of reports of such transient responses the offset of repeated or steady-state stimulation. In either case, the rectifying nonlinearity of a positive response to both stimulus onsets and offsets goes far beyond any nonlinear properties of the hemodynamic models per se, and implies the operation of a pronounced (rectifying) nonlinearity in the underlying neural response to these stimulation conditions.…”
Section: Discussionmentioning
confidence: 96%
“…However, studies of multiple different response waveforms (Zacks et al, 2001;d'Avossa et al, 2003;Bellgowan et al, 2003;Calhoun et al, 2004a;Fox et al, 2005) have typically identified different cortical regions with differential response dynamics to the same or different stimulus conditions. The issue of multiple components within a given region of cortex is not addressed in these studies.…”
Section: Boldðtþ ¼ Gðnðtþþ ð3þmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have been motivated by the hypothesis that if the brain is undertaking processing that relates to event boundaries, transient changes in brain activity should be observed at those points in time corresponding to event boundaries -whether or not you are attending to event segmentation. In one study [18], participants passively viewed short movies of everyday activities while their brain activity was recorded with fMRI. During the initial viewing and fMRI data recording, participants were asked simply to watch the movies and try to remember as much as possible.…”
Section: Neurophysiological Evidence For Automaticity Of Event Segmenmentioning
confidence: 99%